ISOLASI SENYAWA ANTIOKSIDAN DARI EKSTRAK TERPILIH HERBA KITOLOD (LAURENTIA LONGIFLORA (L). PETERM) - Rismawati Eka Sakti, Endah
Background and objectives: Exposure of excess free radicals from the Internal and external factors, causes body can not inhibit free radicals activity. This condition can damage the body organs, which is referred as oxidative stress. Some researchs revealed that oxidative stress had important role in the pathophysiology of diseases, such as atherosclerosis, chronic renal failure, cancer and diabetes mellitus. Antioxidant prevents tissue damage which is caused by free radicals. Kitolod (Laurentia longiflora (L). Peterm) has been used empirically in Indonesian society to cure eye pain and using to treat snake bites, cancer, as a local anesthetic by herbalist medicine in China. Some researchs exposed correlation between antimicrobial, anticancer activity and antioxidant activity. The purpose of this research was to test the antioxidant activity of extracts of kitolod with different polarities of solvents in inhibiting of free radical DPPH (22 diphenyl - I — picrylhydrazyl), determination of total phenolic, flavonoid, carotenoid, determine the corelation among total phenol, total flavonoids and total carotenoids against DPPH activity, and to isolate antioxidant c.omnound from kitolod herbs extract. Methods: The extract was obtained by reflux using three different polarities solvents (n - hexane, ethyl acetate and ethanol). Each extracts were monitored bv thin-layer chromatography (TLO. Antioxidant activity by DPPH method, IC50 of DPPH scavenging activity, determination of total phenolic, flavonoid and carotenoid content were performed by spectrophotometry uv visible anu COiTC1atiOii DPP11 scavenging Activity by Pearson method. Isolation of antioxidant compound was conducted using selected extract. Fractionation was done by using vacuum liquid chromatography with gradient elution (n—hexane ethyl acetate- methanol). The obtained fractions were monitored by TLC. Separation and purification was done by radial chromatography and crystallization. The purity isolates was observed by twodimensional thin-layer chromatography. Characterization of isolates were performed by using spectroscopy (UV - Vis spectrophotometry , IH - NMR , 13C - NMR , HSQC and HMBC). Results: Ethyl acetate herbs extract of kitolod had the highest DPPH scavenging activitiy (50.27 %) and the lowest IC50 of DPPH scavenging activity (47.60 pg/mL). Ethyl acetate extract had the highest total phenolic (5.67 g GAE/IOO g) and the highest total flavonoid (2.66 g QE/IOO g), while the highest carotenoid total was given by n-hexane extract (19.64 g BET/IOO g). Total phenol and carotenoid between n-hexane extract, ethyl acetate extract and ethanol extract had a significant difference While total flavonoid, there are no significant differences between extracts of n-hexane and ethyl acetate extracts, but both are significantly different from the ethanol extract (p<0.05)- Total flavonoid and phenolic extracts of herbs kitolod had positive correlation, and significantly higher contribution activity against DPPH. Two antioxidant compounds had been isolated from ethyl acetate herbs extract of kitolod were (A) white crystal and (B) red crystal. Based on TLC using ß-carotene standard, and elucidation spectroscopy data that compared with ß-carotene data in literature, isolate B was predicted ß-carotene, while isolate A was supposed to be pentacyclic triterpenoid compound, that had maxilllum 242 nm, had 36 atom and —C-O-, carbonyl (ester) (C=O) functional groups and 1 double bound (CH=CH). Conclusion: Ethyl acetate herbs extract of kitolod had higher DPPH scavenging activity than n-hexane extract and ethanolic extract. Total flavonoid and total phenol had positive correlation, and significantly higher activity against DPPH. Two antioxidant compounds that were isolated from ethyl acetate extract were isolate A was supposed to be pentacyclic triterpenoid compound that contained 36 atom C and had —C-O, carbonil (ester) (C=O) groups, with 1 double bound (CH=CH) and isolate B was predicted as ß-carotene.